Assessment of Office-Based Care of Sexually Transmitted Diseases and Vaginitis and Antibiotic Decision-Making by Obstetrician-Gynecologists - J. A. McGregor; W. D. Hager; R. S. Gibbs; L. Schmidt; J. Schulkin (Hindawi Limited, 1998)
Objective: Survey office-based obstetric-gynecologic practitioners regarding their knowledge of infectious disease care and antibiotic use.